Publisher Correction: Genome-wide identification and expression analyses of the homeobox transcription factor family during ovule development in seedless and seeded grapes. Issue 1 (December 2017) - Li, Yunduan; Zhu, Yanxun; Yao, Jin; Zhang, Songlin; Wang, Li; Guo, Chunlei; van Nocker, Steve; Wang, Xiping
A correction to this article has been published and is linked from the HTML version of this paper. The error has been fixed in the paper.